Assessment of intellectual property (IP) management of Industrial Technology Development Institute (ITDI) - Tuazon, Joannalene T.; Posadas, Roger D. (Quezon City University of the Philippines Diliman, 2014)
This project is a research study that aims to assess the IP management of ITDI. Because of the low generation of patented technologies in the institute, practices in the firm are observed and compared to a well-known foreign firm that excel in IP activities such as ITRI of Taiwan and ETRI of Korea. Data gathering was conducted through acquirement of information in the science journals, research, related studies, and other publication on the internet. Moreover, primary data was gathered through interview, questionnaire, and survey in the researchers of ITDI and member of patent committee. ITDI lacks the capability to implement an effective IP management due to deficiency in the financial support for promoting IP activities. It is the main source of the weaknesses of the firm to support the growth for IP culture. While, the source of competency lies on its human resource that are very dedicated to its work and is eager to create quality technologies. The resulting consequences for the absence of allocated budget for IP is that there is no lawyer available for IP consultation, the institute is not capable to conduct IP audit and IP valuation, it also not also undertaking market research, not capable to defend itself against litigation, and could not file infringement against illegal user of its technology. On the other hand, member of the IP committee are flexible enough to include the additional job aside from its daily task. Whereas, researchers have initiative on focusing on technologies with existing market needs and could be patentable even under utility model. Therefore, ITDI needs financial resources to further promote the IP culture in the management system of the institute. It will strengthen the capability of the firm to create useful technologies considering the protection of the invention. Thus, also provide opportunity to the institute to generate income through technology licensing and also provides opportunity to the local industries to become more competent in the global market.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Industrial Technology Development Institute (Philippines); Intellectual property -- Management